Effect Of Compensation And Job Satisfactionon Employee Performance In Ud Andalas Industri Krupuk In Malang District - Nirmala, Aida Ayu Natasha; Irbayuni, Sulastri (Jurnal Ekonomi Balance, 2022)
Employee performance is one of the important factors for the success of an organization or company. On this basis, the purpose of this research is to find out (1) the effect of compensation on employee performance, and (2) the effect of job satisfaction on employee performance at UD Industri Krupuk Andalas in Malang District. The population in this study were employees of UD Industry Krupuk Andalas in Malang District. Sampling in this study used a saturated sampling technique of 40 employees of marketers at UD Industri Krupuk Andalas in Malang District. The type of data used in this research is primary data obtained from the distribution of questionnaires. This research uses data analysis technique Patrial Least Square (PLS). The results of this study indicate (1) Compensation can contribute to the performance of the employees of UD Industri Krupuk Andalas in Malang District. It is identified that the provision of fair and good compensation will have an increasing impact on employee performance, and (2) Job satisfaction can contribute to the performance of UD Industri Krupuk Andalas employees in Malang District. This identifies if the level of high employee job satisfaction will have an increasing impact on employee performance.